Metal Doping to Enhance the Photoelectrochemical Behavior of LaFeO3 Photocathodes. Issue 11 (8th May 2017) - Díez‐García, María Isabel; Gómez, Roberto
Abstract: The development of tandem devices for water photosplitting requires the preparation of photocathodic materials based on earth‐abundant elements that show long‐term stability in aqueous electrolytes. Ternary metal oxides seem to be a viable option, among which perovskites stand out. In this context, transparent and compact LaFeO3 thin‐film electrodes have been prepared by a sol–gel process, both undoped and doped with metals (M) such as Mg or Zn. Pristine electrodes support the development of cathodic photocurrents in 0.1 m NaOH aqueous solutions, particularly in the presence of oxygen, with an onset potential as high as 1.4 V versus the reversible hydrogen electrode. Doping with Mg or Zn leads to an important enhancement of the photocurrent, which peaks for a stoichiometry of LaFe0.95 M0.05 O3 with a sixfold enhancement with respect to the pristine material. Such an improvement is attributed to an increase in both the density and mobility of the majority carriers, although a contribution of surface passivation cannot be excluded. Abstract : Doping is the answer : Mg‐ and Zn‐doping of LaFeO3 constitutes a step toward stable and efficient earth‐abundant metal oxide photocathodes for artificial photosynthesis. A significant multiplication of the photocurrent is observed, particularly for oxygen reduction, without paying the price of low stability.